2018
DOI: 10.1038/s41598-018-27607-7
|View full text |Cite
|
Sign up to set email alerts
|

Hexane-Isopropanolic Extract of Tungrymbai, a North-East Indian fermented soybean food prevents hepatic steatosis via regulating AMPK-mediated SREBP/FAS/ACC/HMGCR and PPARα/CPT1A/UCP2 pathways

Abstract: This study for the first time examined the prophylactic role of Tungrymbai, a well-known fermented soybean food of North-East India, against hepatic steatosis. Treatment with hexane-isopropanolic (2:1, HIET) but not hydro-alcoholic (70% ethanol, HAET) extract dose-dependently (0.1, 0.2, or 0.3 µg/mL) reduced the intracellular lipid accumulation as shown by lower triglyceride levels and both Oil Red O and Nile Red staining in palmitate (PA, 0.75 mM)-treated hepatocytes. Immunobloting, mRNA expression, and knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…There is no prior evidence about the regulation relationship of the phosphorylation status of AMPK with MLD in fish, but previous studies found that fatty acid treatment or lipid-enriched diet inhibited AMPK phosphorylation and AMPK activation suppressed lipogenesis in rainbow trout (Polakof et al, 2011; Libran-Perez et al, 2015; Velasco et al, 2018). SREBP1 is a key transcription factor regulating lipogenesis and ACC and FASN are its downstream genes (Dihingia et al, 2018). It was well documented that hepatic lipid accumulation was closely related to the induction of SREBP1 expression (Pai et al, 2013) and AMPK/SREBP pathway had critical functions in the development of MLD (Kohjima et al, 2008; Jung et al, 2011; Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no prior evidence about the regulation relationship of the phosphorylation status of AMPK with MLD in fish, but previous studies found that fatty acid treatment or lipid-enriched diet inhibited AMPK phosphorylation and AMPK activation suppressed lipogenesis in rainbow trout (Polakof et al, 2011; Libran-Perez et al, 2015; Velasco et al, 2018). SREBP1 is a key transcription factor regulating lipogenesis and ACC and FASN are its downstream genes (Dihingia et al, 2018). It was well documented that hepatic lipid accumulation was closely related to the induction of SREBP1 expression (Pai et al, 2013) and AMPK/SREBP pathway had critical functions in the development of MLD (Kohjima et al, 2008; Jung et al, 2011; Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It was well documented that hepatic lipid accumulation was closely related to the induction of SREBP1 expression (Pai et al, 2013) and AMPK/SREBP pathway had critical functions in the development of MLD (Kohjima et al, 2008; Jung et al, 2011; Li et al, 2011). AMPK phosphorylation attenuated hepatic steatosis and fatty liver disease, etc., by inhibiting the expression of SREBP1, and further the inhibition of ACC and FASN (Li et al, 2011; Lee et al, 2015; Dihingia et al, 2018). The increased cAMP, up-regulated P-AMPK protein and depressed mRNA level of SREBP1, ACC, and FASN demonstrated that cAMP/AMPK/SREBP1 was an important pathway to decrease hepatic lipid accumulation by dietary BA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, the present results indicate that AMPK is one of the main targets of Ato involved in the preventive effects of Ato on NAFLD. Numerous previous studies have indicated that PPARα is downstream of AMPK and Akt, and that its expression level is regulated by Akt (27)(28)(29). Therefore, the mRNA and protein expression levels of PPARα and PPARGC1A were investigated in the liver tissues of the hamsters in the present study.…”
Section: Ato Inhibits Lipid Accumulation Via the Ampk-dependent Upregmentioning
confidence: 93%
“…The energy sensor AMP-activated protein kinase (AMPK) is a key player in the regulation of energy metabolism [14151617] through its repression of fatty acid and TG synthesis [18]. Importantly, AMPK regulates hepatic lipid metabolism via the phosphorylation of its well-recognized downstream target ACC [19202122].…”
Section: Introductionmentioning
confidence: 99%